PENGARUH STRUKTUR AUDIT, PENGALAMAN, KESESUAIAN PERAN DAN INDEPENDENSI TERHADAP KINERJA AUDITOR INTERNAL PEMERINTAH DAERAH - Geofanny Geofanny; Sri Yuni (Universitas Palangka Raya, 2021)
This study aims to determine of the effect of audit structure, experience, appropriateness of roles and independence on the performance of local government internal auditors (Empirical Studies at the Inspectorate of Central Kalimantan Province, Palangka Raya City and South Barito District) sample Kalimantan Province there were 54 respondents, Inspectorate of Palangka Raya City had 9 respondents and Inspectorate of Barito Selatan Regency had 10 respondents,number of auditors was 73 respondents.Data analysis used SPSS 25.This (1) the audit structure has no effect on the performance of local government internal auditors (2) Experience has no effect on the performance of audito (3) Suitability of roles has a positive effect on the performance of local government internal auditors.(3) Independence has a positive effect on the performance of local government internal auditors. (4) The results of the audit structure hypothesis testing, experience of role suitability and independence on the performance of the local government internal auditors simultaneously have a positive effect